Strategi Komunikasi Orang Tua Mengatasi Kecanduan Belanja Online Di Shopee (Studi Kualitatif Deskriptif Pada Mahasiswa Universitas Dharma Andalas) - Okta Tiara Rahmi; Ria Edlina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Online shopping addiction among students has become a phenomenon with easy access and various promotions offered by Shopee, making students tend to buy unnecessary items until they get trapped in debt due to the Shopee Paylater feature service, resulting in financial problems that ultimately use tuition fees to pay off debts. The purpose of this study is to describe the communication strategies implemented by parents in overcoming online shopping addiction, especially on the Shopee platform, experienced by Dharma Andalas University students. The research method used in this study is a qualitative study with a descriptive approach. The data used are observation methods, semi-structured interviews, and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. The theory used in this study is the Family Communication theory. The results of this study indicate that in an effort to overcome online shopping addiction in children, parents have several communication strategy patterns. There are four communication patterns used by parents in dealing with children who are addicted to online shopping, namely, a consensual pattern involving open communication between parents and children, a pluralistic pattern with openness in the family, where children are given space to be honest about the problems they face. Parents can provide guidance and appropriate solutions to prevent children from stress due to online shopping debt. The protective pattern emphasizes children's compliance with family rules. Parents ask children to delete the Shopee application as a step to stop uncontrolled shopping habits. Furthermore, the Laissez-faire pattern shows a lack of parental involvement in communication, therefore it is important for parents to improve communication in the family and provide emotional support so that children are better able to deal with problems.Keywords: Communication Strategy, Online Shopping Addiction, Shopee Paylater, Family Communication, Parents